An observational study of clinical outcomes of everolimus-eluting bioresorbable scaffolds comparing the procedural use of optical coherence tomography against angiography alone. Issue 6 (September 2018) - Hamshere, Stephen; Byrne, Alex; Guttmann, Oliver; Rees, Paul; Bourantas, Christos; Weerakody, Roshan; Wragg, Andrew; Knight, Charles; Mathur, Anthony; Jones, Daniel A.
Abstract : Objectives: The introduction of the bioresorbable vascular scaffold (BVS) has led to new avenues of coronary intervention; however, there have been concerns raised regarding the mechanical properties of BVS and the resulting in-stent thrombosis. We aim to assess whether intracoronary imaging improves outcome in patients following BVS implantation. Patients and methods: All patients undergoing percutaneous coronary intervention using BVS at a single centre between June 2013 and June 2016 were included in this study ( n =79). Percutaneous coronary intervention with BVS was performed according to conventional practice: predilatation, postdilatation and intracoronary assessment with optical coherence tomography (OCT) according to operator's preferences. The primary endpoint was Major Adverse Cardiovascular Events (MACE), defined as all-cause mortality, myocardial infarction and revascularization, at 120 days. Results: Forty-three (54.4%) patients underwent OCT assessment and 36 (45.6%) patients underwent angiography alone post-BVS insertion. There were no significant differences at baseline between both groups; a total of 13 (30.2%) patients who had intracoronary OCT imaging performed underwent further postdilatation after malapposed struts were identified. Although no deaths were observed, there was a significant difference seen in MACE over the follow-up period between OCT and angiography cohorts (4.7 vs. 19.4% respectively; P =0.042). There was a greater number of MACE in low-experienced operators. Conclusion: As visual assessment with angiography has poor specificity for identifying strut malapposition, intracoronary OCT should be undertaken in all patients postinsertion of BVS stents in inexperienced operators to appropriately assess for stent malapposition, and reduce the subsequent risk of MACE.